Outcome after seizure recurrence on antiepileptic drug withdrawal following temporal lobectomy. (17th July 2018) - Rathore, Chaturbhuj; Jeyaraj, Malcolm K.; Dash, Gopal K.; Wattamwar, Pandurang; Baheti, Neeraj; Sarma, Sankara P.; Radhakrishnan, Kurupath
Abstract : Objective: To study the long-term outcome following seizure recurrence on antiepileptic drug (AED) withdrawal after anterior temporal lobectomy for mesial temporal lobe epilepsy. Methods: We retrospectively studied the AED profile of patients who had a minimum of 5 years of postoperative follow-up after anterior temporal lobectomy for mesial temporal lobe epilepsy. Only those patients with hippocampal sclerosis or normal MRI were included. AED withdrawal was initiated at 3 months in patients on ≥2 drugs and at 1 year for patients on a single drug. Results: Three hundred eighty-four patients with median postoperative follow-up of 12 years (range, 7–17 years) were included. Of them, 316 patients (82.3%) were seizure-free during the terminal 1 year. AED withdrawal was attempted in 326 patients (84.9%). At last follow-up, AEDs were discontinued in 207 patients (53.9%). Seizure recurrence occurred in 92 patients (28.2%) on attempted withdrawal. After a median postrecurrence follow-up of 7 years, 79 (86%) of them were seizure-free during the terminal 2 years. AEDs could be stopped in 17 patients (18.5%) and doses were reduced in another 57 patients (62%). Patients with febrile seizures, normal postoperative EEG at 1 year, and duration of epilepsy of <20 years (FND20 score) had 17% risk of seizure recurrence on attempted AED withdrawal. We also formulated a score to predict the chances of AED freedom for the whole cohort. Conclusion: Patients with seizure recurrence on AED withdrawal have good outcome with 86% becoming seizure-free and 18% becoming drug-free after initial recurrence. A FND20 score helps in predicting recurrence on AED withdrawal.